2016
DOI: 10.1002/bjs.10127
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-infiltrating CD8 to FOXP3 lymphocyte ratio in predicting treatment responses to neoadjuvant chemotherapy of aggressive breast cancer

Abstract: pCR).Results: A total of 177 patients were included, of whom 90 had a high CFR and 87 a low CFR. Triple-negative breast cancer (TNBC) was more common in the high-CFR group than in the low-CFR group (46 versus 23 per cent; P = 0⋅002), as was HER2-enriched breast cancer (HER2BC) (27 versus 14 per cent; P = 0⋅033). Among these patients, the pCR rate was significantly higher in the high-CFR group than in the low-CFR group (TNBC: P = 0⋅022; HER2BC: P < 0⋅001). In multivariable analysis high-CFR status was an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 34 publications
6
90
0
1
Order By: Relevance
“…A higher CD8+/FOXP3+ TILs ratio has been related to favorable prognosis in aggressive breast cancer, ovarian cancer and osteosarcoma [16][17][18]. Similarly, we observed that the prognostic value of this ratio is better than that of FOXP3+ or CD8+ TILs alone, which partly reflects reciprocal interactions between promotive CD8+ TILs and repressive FOXP3+ TILs (Tregs) in tumors [19,20].…”
Section: Discussionsupporting
confidence: 49%
“…A higher CD8+/FOXP3+ TILs ratio has been related to favorable prognosis in aggressive breast cancer, ovarian cancer and osteosarcoma [16][17][18]. Similarly, we observed that the prognostic value of this ratio is better than that of FOXP3+ or CD8+ TILs alone, which partly reflects reciprocal interactions between promotive CD8+ TILs and repressive FOXP3+ TILs (Tregs) in tumors [19,20].…”
Section: Discussionsupporting
confidence: 49%
“…Among these factors, the development of lung adenocarcinoma is controlled by a biological system that depends on genetic factors as well as the interplay between tumor cells, stromal cells, and host immune cells (7). Immune system invasion and/or escape is essential in the etiology of lung adenocarcinoma, and the presence of tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment is an indication of the host immune response to tumor antigens (8). TILs comprise a variety of immune cells, including CD4 + T lymphocytes, CD8 + lymphocytes, FOXP3 + regulatory T cells, natural killer (NK) cells, dendritic cells and macrophages (9).…”
Section: Original Articlementioning
confidence: 99%
“…TILs comprise a variety of immune cells, including CD4 + T lymphocytes, CD8 + lymphocytes, FOXP3 + regulatory T cells, natural killer (NK) cells, dendritic cells and macrophages (9). TILs are attracting attention for their use in monitoring the immune response in the tumor microenvironment and predicting the prognosis and treatment response in several cancers, such as colorectal and breast cancers (8,9). Therefore, in the present study, we proposed that the infiltration of lymphocytes in lung adenocarcinoma and expression of chemokine receptors might be correlated with tumor differentiation, TNM stage, clinical stage, disease-free survival (DFS) or overall survival (OS).…”
Section: Original Articlementioning
confidence: 99%
“…In particular, it has been demonstrated that T cells and cancer cell phenotypes associated with a poor antitumor response display abnormal expression of programmed cell death protein (PD)-1, programmed death ligand-1 (PD-L1), PD-L2, and forkhead box P3 (FOXP3) (8).…”
mentioning
confidence: 99%